Malignant transformation of benign thyroid nodule is caused by prolonged H2O2 insult that interfered with the STAT3 pathway? - Lee, Ching Chin; Abdullah, Mardiaty Iryani; Mat Junit, Sarni; Ng, Khoon Leong; Wong, Sing Ying; Ramli, Nur Siti Fatimah; Hashim, Onn (e-Century Publishing Corporation, 2016)
Approximately 60% of papillary thyroid cancer (PTC) cases in Malaysia occur as a result of long-standing benign thyroid nodules. However, the underlying mechanisms that led to the malignant transformation are not understood. Methods & Results: Here, we report a study of benign and malignant thyroid tissues of a Malay woman presented with concurrent benign thyroid cyst and PTC. The same patient had only presented with neck swelling five years earlier. Whole-exome capture sequencing of extracted DNA from the PTC tissue revealed mutations of 1799 T>A (p.V600E) and c.353 G>A (p.R118Q) in the V-Raf Murine Sarcoma Viral Oncogene Homolog B (BRAF) and the Thyrotropin-Releasing Hormone (TRH) genes, respectively. When the benign cyst of the patient was subjected to direct PCR screening for both the mutations, only the c.353G>A mutation of the TRH gene was detected. Both the benign and malignant tissues also showed decrease or loss of expression of multiple iodide metabolism genes with elevated BRAF expression. Analyses by 2-dimensional electrophoresis and Ingenuity Pathway algorithm indicated “reactive oxygen species insult”, “tissue injury/inflammation”, “cell proliferation” and “apoptosis and necrosis inhibitions” in the benign cyst. Both the benign and PTC tissues demonstrated different expression patterns of activated signal transducer and activator of transcription 3 (pY-STAT3), with the former tissue expressing a novel putative STAT3 isoform termed STAT3ε. Discussion: The data of our study, when taken together, appear to suggest that prolonged H2O2 insults in the patient might have resulted in extreme oxidative stress that interfered with the MAPK and STAT3 pathways, which then led to BRAFV600E mutation and consequential loss of function of p53 as well as the altered metabolisms and malignant transformation that occurred in PTC.